Mechanistic Study on the Selective Oxidation of Acrolein to Acrylic Acid concerning the Role of Water - Knoche, Stefan; Heid, Maurice; Gora, Niklas; Ohlig, Dominik; Drochner, Alfons; Etzold, Bastian J.M.; Vogel, Herbert (ChemCatChem, 2020)
The activity of Mo/V/W mixed oxide catalyst in the gas phase oxidation of acrolein to acrylic acid is tremendously influenced by addition of fed water. This effect of water is investigated and connected to the catalytic mechanism by several stationary kinetic measurements and transient response methods, such as temperature-programmed reduction, oxidation and desorption experiments, special concentration-programmed methods as well as H218O-SSITKA and D2O-SSITKA experiments. Furthermore, kinetic modeling, based on results of H218O-SSITKA experiments in a wide temperature and feed water content range gives access to kinetic parameters of single reaction steps in the catalytic mechanism. The developed mechanism is not only able to describe conversion and selectivities, inclusively the effect of water, but also describes the 18O-degree of labeling of all reaction components quantitatively.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Acrolein; Acrylic Acid; Isotopic labeling; Mo-V-oxides; Transient response methods